A Slack approach to optimised modularisation of prefabricated structures using a multi-variable modularisation index. (October 2021) - Tidhar, N.; Li, Y.; Kristombu Baduge, K.S.; Mendis, P.; Thilakarathna, P.S.M.; Chandrathilaka, E.R.K.
Highlights: Modularisation solutions may be found using a recursive Slack-distribution algorithm. The performance of each solution may be evaluated using a multi-variable index. The index comprises of three weighted Objective Functions (Cost, Speed, and Quality). Compared to manual methods, the accuracy of the proposed method is significant. Abstract: The construction industry is currently undergoing an increasing demand to boost productivity and improve system efficiencies. Clients are demanding increasingly more customised products at a more competitive cost, speed, and quality. Yet current design systems and existing literature largely overlook the use of automated decision-making tools for supporting mass-customisation for prefabricated buildings. To address this gap, a method for using automated tools to optimise the modularisation of prefabricated light-weight structures is investigated. This study's primary contributions include a multi-variable Modularisation Index, which offers a novel framework for characterising the "optimal" solution, and a recursive Slack-distribution algorithm, which offers a novel method for modularising customised architectural designs. The core insight is that an optimal modularisation solution may be found using a Greedy algorithm. This involves incrementally adjusting the internal module boundaries from the initial solution, and evaluating each viable solution using the proposed Modularisation Index. The Index considers functions of cost, speed, and quality that are weighted according to client preferences. The system outputs the top three highest scoring modularisation solutions which may then be examined by the builder. Overall, the proposed method performs equal to or better than experts for 90% of cases. The Index and modularisation algorithm hence offer useful tools for automating and optimising prefabricated construction, with further opportunity for optimising architectural designs.